Investigation on the low temperature oxidation of light oil for safely enhancing oil recovery at high temperatures and pressures. (1st June 2020) - Li, Pengliang; Liu, Zhenyi; Li, Mingzhi; Zhao, Yao; Li, Xuan; Wan, Song; Ma, Yuanyuan; He, Yanghua
Abstract: Air injection is an important method for tertiary oil recovery. Air with high temperature and pressure will affect the properties of crude oil. It will also affect the oxidation reaction between crude oil and oxygen. As a result, the liquidity of crude oil and safety of air injection process will be influenced. In this study, experiments on oil samples from Liaohe oilfield were carried out to investigate the effect of high temperature and pressure on the properties of crude oil. The viscosity and component change of crude oil were analysed. Besides, the change of gas components after reaction was also investigated. The results showed that the viscosity of crude oil increased with the increase of reaction time, which was caused by the increase of asphaltene in crude oil. The viscosity of crude oil also showed an upward trend with the increase of temperature and pressure. Interestingly, when the pressure reached 20 MPa, the viscosity of crude oil experienced a decrease. Besides, the oxygen concentration declined as the temperature rose up from 80 °C to 140 °C. Therefore, to ensure safety and better liquidity of crude oil, the temperature and pressure should be controlled in certain range during air injection. Highlights: Experiments on the low temperature oxidation of crude oil were carried out at different pressures and temperatures. Effects of pressure and temperature on the properties of crude oil and exhaust gas were comprehensively analysed. Better pressure and temperature conditions of injected air were obtained. Pressure should be controlled within 15 MPa to make the crude oil have better liquidity. Temperature should be controlled between 130 °C and 140 °C to ensure the safety of air injection process.